Sagrado e Cultura no Mundo Secularizado = Sacred and culture in the secularized world - Barsalini, Glauco (Estudos teológicos, 2022)
WESTPHAL, Euler Renato. Secularization, Cultural Heritage and the Spirituality of the Secular State: Between Sacredness and Secularization. 1. ed. Paderborn: Brill/Verlag Ferdinand Schöningh, 2019. v. 1. 119 p.